(4w-8)+(3w+6)=180
7w-2=180
7w=180+2
7w=182
w=26
The pictures may be in a different order for you but it’s the 3rd graph where the minimum is (-4,-1)
Answer:
(The solution is (4, -11).
Step-by-stp explanation:
Let f(x) = g(x) = y:
y = 3x − 23
y = -4.5x + 7 Subtract the second equation from the first to eliminate y:
0 = 7.5x - 30
7.5x = 30
x = 4
Plug this into the first equation:
y = 3(4) - 23
y = -11.
In order to visualize the transformations, we must execute the transformation in the options
The first transformation would shift triangle ABC 3 units to the left and reflect it across x = 4. This will not map ABC unto DEF.
The second transformation would shift triangle ABC 7 units down and reflect it across x =4. This will map ABC unto DEF,
So, the answer is the second option.
Answer:
11x^2-8x-14
Step-by-step explanation:
(2x^2- 8x– 6)+(9x^2-8) = 11x^2-8x-14